2021
DOI: 10.3390/v13020147
|View full text |Cite
|
Sign up to set email alerts
|

Novel Flavivirus Attenuation Markers Identified in the Envelope Protein of Alfuy Virus

Abstract: Alfuy (ALFV) is an attenuated flavivirus related to the Murray Valley encephalitis virus (MVEV). We previously identified markers of attenuation in the envelope (E) protein of the prototype strain (ALFV3929), including the hinge region (E273–277) and lack of glycosylation at E154-156. To further determine the mechanisms of attenuation we assessed ALFV3929 binding to glycosaminoglycans (GAG), a known mechanism of flaviviruses attenuation. Indeed, ALFV3929 exhibited reduced binding to GAG-rich cells in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Other studies revealed that the Lys 70 residue was present in multiple commonly used SINV laboratory strains [51]. This phenomenon has been reproduced starting with low cell passage versions of RRV, Semliki Forest virus (SFV) and CHIKV alphaviruses and YFV, MVEV, DENV, WNV, JEV, and TBEV flaviviruses yielding a large panel of known loci associated with enhancement of GAG interaction after in vitro passage () () [53, 57, 60, 66, 72, 73, 75, 85, 88, 93–97]. These findings have utility in live attenuated vaccine design and also may allow determination of differences in naturally acquired and cell-adaptive GAG binding characteristics.…”
Section: Introductionmentioning
confidence: 94%
“…Other studies revealed that the Lys 70 residue was present in multiple commonly used SINV laboratory strains [51]. This phenomenon has been reproduced starting with low cell passage versions of RRV, Semliki Forest virus (SFV) and CHIKV alphaviruses and YFV, MVEV, DENV, WNV, JEV, and TBEV flaviviruses yielding a large panel of known loci associated with enhancement of GAG interaction after in vitro passage () () [53, 57, 60, 66, 72, 73, 75, 85, 88, 93–97]. These findings have utility in live attenuated vaccine design and also may allow determination of differences in naturally acquired and cell-adaptive GAG binding characteristics.…”
Section: Introductionmentioning
confidence: 94%
“…A GAG molecule is a negatively charged polysaccharide, well known as an attenuation factor of flaviviruses [ 23 ]. GAG-binding sites are mainly located in the domain III of the E protein and they continue to be discovered [ 24 ]. Moreover, there is a report on a putative GAG-binding site (E138 in Japanese encephalitis virus) in the domain I [ 25 ].…”
Section: Discussionmentioning
confidence: 99%